Seasonality and aquatic metacommunity assemblage in three abandoned gold mining ponds in the southwestern Amazon, Madre de Dios (Peru) - Julio M. Araújo-Flores (Elsevier, 2021)
Worldwide demand for gold has caused increased extractive activities in the Western Amazon, resulting in a wide-scale transformation of the Madre de Dios river basin (Peru) due to Artisanal and Small-scale Gold Mining (ASGM). These impactful activities profoundly affect the natural landscape and hydroscape as terra firme forest and floodplain habitats are deforested leaving a vast landscape of abandoned ponds that are subsequently colonized from surrounding water bodies. However, the metacommunity dynamics of these emergent networks of connected wetlands and their environmental drivers remain virtually unknown. Here, we present a one-year (May 2017–May 2018) study conducted to assess the composition, abundance and trophic structure of fish assemblages in three abandoned ASGM ponds and their interactions in relation to those of other freshwater groups (macroinvertebrates, phytoplankton and zooplankton). We aimed to determine the influence of environmental parameters on community composition, focused on flood pulse influence (FPI), seasonality, and to identify indicators for predicting aquatic communities’ assemblages. A remarkably abundance and diversity were found totaling 4601 sampled fish from 6 orders, 27 families, 68 genera and 103 species, as well as 87 macoinvertebrate, 71 phytoplankton and 44 zooplankton taxa. The two FPI ponds showed a more stable fish trophic structure throughout the year than the unique non-FPI, probably due to the floods provision of buffer against the lack of resources that occurs during the dry season. Conversely, fish of higher trophic levels were not detected during the dry and transition-to-wet seasons in the non-FPI pond surveyed. Community trajectory analysis showed greater stability of fish assemblages in the non-FPI pond compared to the FPI ponds, which experienced larger disturbance of environmental parameters and biotic inputs during flooding events. Detrended correspondence analysis showed floods as the key factor influencing aquatic communities and species accumulation. However, whereas floods had a large influence on fish and macroinvertebrates, seasonality was the main driver for plankton. FPI ponds showed six-fold higher fish and macroinvertebrate species richness than non-FPI ones, while plankton showed an opposite trend. FPI was the main factor determining the taxonomic composition of fish, followed by dissolved oxygen. Macroinvertebrates were also affected by FPI together with pH and the presence of grassed banks, while conductivity determined phytoplankton composition. Our study presents novel evidence on the highly heterogeneous communities of ASGM abandoned ponds, highlighting their important ecological value and potential role in providing of ecosystem services currently overlooked from conservation policies and management of the aquatic resources.